Peran Lembaga Penegak Hukum dalam Penerapan Undang Undang Nomor 13 Tahun 2006 tentang Perlindungan Saksi dan Korban terhadap Perlindungan Hak Atas Keamanan Pribadi bagi Saksi dan Korban dalam Sistem Peradilan Pidana - Fitriyani, Fitriyani (Jurnal HAM, 2010)
The aim of this paper is to find out the practice conducted by the law enforcement institutions in implementing the Law No. 13 of the year 2006 on The Protection of Witness and Victim. The method used in this paper is descriptive qualitative which based on secondary data that is the research done at four provinces (Provinces of Papua, Bali, Nort Sumatera, and South Sulawesi). The result of the research shows that the mechanism of the witness and victim protection conducted by the law enforcement institutions (the police, district attorney and the court) have not given the maximum protection yet as the implementation of protection on the rirgt of personal security by the state. This condition is caused by the unavailable of the regulation to ensure the authority, mechanism, the form of protection and funding by the law enforcement institutions.   With the existence of  the Law No. 13 of the year 2006 on The Protection of Witness and Victim  so the protection of the witness and victim as the implementation of the protection of the right of personal security will be more guaranted. In fact on lack of capacity from the law enforcement institutions, so that the police, district attorney and the court should work together with the Instution of Witness and Victim Protection, as the institutions formed based on the Law No. 13 of the year 2006, and other institutions that have function in witness and victim protection in order that the right on the protection of personal security of the citizen in the area of criminal justice process can be guaranted.